2012
DOI: 10.1055/s-0032-1315208
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Herpes Simplex Virus Type 1 by Thymol-Related Monoterpenoids

Abstract: This study examined the anti-herpes simplex virus type I activity of the major constituents of several essential oils. Plaque reduction assays were performed to evaluate anti-herpes simplex virus type I activity. Thymol and carvacrol both possessed significant antiviral activity with an IC₅₀ of 7  µM, and herpes simplex virus type I was 90 % inactivated within 1 hr. The mode of antiviral action was shown to affect the virion directly. Evidence was also observed by electron microscopy. Evaluation of the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 10 publications
3
43
0
4
Order By: Relevance
“…A novel finding is the anti‐HSV‐2 activity of cinnamaldehyde (SI: 28.3) reported here for the first time. Finally, the anti‐HSV‐2 activity of carvacrol (SI: 12.1) confirmed previous findings by Pilau et al () and Lai et al (). As shown in Figure , carvacrol and cinnamaldehyde were also found as components of the EO; however, this was not the most active phytopreparation.…”
Section: Resultssupporting
confidence: 90%
“…A novel finding is the anti‐HSV‐2 activity of cinnamaldehyde (SI: 28.3) reported here for the first time. Finally, the anti‐HSV‐2 activity of carvacrol (SI: 12.1) confirmed previous findings by Pilau et al () and Lai et al (). As shown in Figure , carvacrol and cinnamaldehyde were also found as components of the EO; however, this was not the most active phytopreparation.…”
Section: Resultssupporting
confidence: 90%
“…Lai et al . reported disruption of the envelope of HSV‐1 (as visualized via TEM) by carvacrol and thymol. Another study reported the disintegration of the envelopes of HSV‐1 and Newcastle disease virus after treatment with oregano and clove oils using TEM imaging (Siddiqui et al .…”
Section: Discussionmentioning
confidence: 99%
“…Wen et al (90) found that two phytocompounds, betulinic acid and savinin, appeared to inhibit postbinding entry of severe acute respiratory syndrome (SARS) coronavirus into cells. Evidence from TEM imaging indicates that some plant antimicrobials may act directly upon the virus envelope (50,53,63).…”
Section: Discussionmentioning
confidence: 99%
“…Many plant essential oils, extracts, and their individual components have been shown to possess antibacterial properties in previous studies (30,34,35,36,37,38,39,40,41). Some have also been shown to have antifungal (30,42,43,44,45) and antiviral (30,46,47,48,49,50,51,52,53,54) properties.…”
mentioning
confidence: 97%
See 1 more Smart Citation